Annulate lamellae and intracellular pathogens. (25th March 2021) - Eymieux, Sébastien; Blanchard, Emmanuelle; Uzbekov, Rustem; Hourioux, Christophe; Roingeard, Philippe
Abstract: Annulate lamellae (AL) have been observed many times over the years on electron micrographs of rapidly dividing cells, but little is known about these unusual organelles consisting of stacked sheets of endoplasmic reticulum‐derived membranes with nuclear pore complexes (NPCs). Evidence is growing for a role of AL in viral infection. AL have been observed early in the life cycles of the hepatitis C virus (HCV) and, more recently, severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), suggesting a specific induction of mechanisms potentially useful to these pathogens. Like other positive‐strand RNA viruses, these viruses induce host cells membranes rearrangements. The NPCs of AL could potentially mediate exchanges between these partially sealed compartments and the cytoplasm. AL may also be involved in regulating Ca 2+ homeostasis or cell cycle control. They were recently observed in cells infected with Theileria annulata, an intracellular protozoan parasite inducing cell proliferation. Further studies are required to clarify their role in intracellular pathogen/host‐cell interactions.